Single dose of intraoperative intravenous morphine for analgesia in children undergoing tonsillectomy: Randomized, double-blind clinical trial - Araújo,Marcus Cavalcante de Oliveira (2022)
Abstract Introduction Children undergoing tonsillectomy have severe pain in the postoperative period. One of the pharmacological options for analgesia is opioids, such as morphine. However, the risks of adverse effects, such as increased recovery time from anesthesia and respiratory depression, can limit its use. Objectives To evaluate the use of intraoperative intravenous morphine to reduce immediate postoperative pain in children undergoing tonsillectomy. Methods In this double-blind randomized study, children aged 3-10 years were submitted to tonsillectomy, with or without adenoidectomy, and divided into two groups. Children in group M received 0.1 mg/kg of intravenous morphine during anesthetic induction, while those in the control group received conventional anesthesia without morphine. Postoperative pain perceptions were assessed at 30, 60, 120, 180 and 240 min after recovery from anesthesia, by the children themselves and also by their parents or guardians, using a facial pain scale. Results A total of 57 children were included, 30 in the group with morphine and 27 in the group without morphine. According to the children themselves, the postoperative pain was less at the evaluations performed at 30 min after awakening from anesthesia (p= 0.023), while according to their parents/guardians, the pain was less intense in the evaluations performed at 30 (p= 0.002), 60 (p= 0.006) and 180 min (p= 0.007) after awakening. Moreover, postoperative analgesics were less requested by children in the morphine group. No observed side effects were associated with the use of morphine. Conclusion A single dose of intravenous morphine during anesthetic induction reduced the intensity of immediate postoperative pain in children undergoing tonsillectomy, without increasing the time of awakening from anesthesia and with lower consumption of rescue analgesics.